Narratives of recovery in people with coexisting mental health and alcohol misuse difficulties. Issue 1 (19th February 2018) - Stott, Andrew; Priest, Helena
Abstract : Purpose: Existing literature has examined what recovery means to people with co-occurring difficulties, but does little to examine experiences of recovery as a process. The purpose of this paper is to use a narrative approach to explore the process of recovery as an individual journey in a social context. It focuses on people who use alcohol in order to explore the impact of alcohol's specific cultural meanings on the recovery journey. Design/methodology/approach: Ten interviews with people with coexisting mental health and alcohol misuse difficulties were conducted, audio-recorded, and transcribed. The transcriptions were analysed using narrative analysis. Findings: Most participants' narratives shared a three-part structure, from a traumatic past, through an episode of change, to an ongoing recovery phase. Change and recovery were attributed to several factors including flexible and practical support from services, therapeutic relationships with key professionals, and peer support. Some participants redefined themselves and their alcohol use in relation to ideas of what it is to be "normal". Research limitations/implications: The research excluded people who recover outside of services, replicating a shortcoming of much research in this area. Practical implications: The value placed on professionals having specialised therapeutic skills in working with trauma highlights the need for training in this area. The role for practical and material support underlines the importance of multi-agency working. Originality/value: The narrative methodology enables the study to draw links between personal stories of recovery and wider social influences, allowing comment on the implications for services. Further, the experiences of people with coexisting mental health and alcohol misuse difficulties have rarely been studied apart from the dual diagnosis population in general, so this paper is able to investigate the specific challenges for this population.